Peran Pengasuhan Terhadap Kepatuhan Pada Anggota Polisi Satuan Sabhara Dipolres X - Melky Situmorang; Yuarini Wahyu Pertiwi (Lembaga Pengembangan Kinerja Dosen, 2023)
Parental care is inseparable from the morals and ways of educating children's behavior, how to make children have behavior that is in accordance with applicable rules and norms, both in the family environment and work environment. Quantitative research type with 85 respondents. .The measuring instrument in this study is a compliance scale, using a modification of measuring instruments from Pertiwi and Muminin (2020), with a total of 12 items, measuring instruments on the parenting scale in this study used modifications to measuring instrument instruments developed by Pertiwi and Muminin (2020) research with a total of 18 items from 27 items. The hypothesis in this study is